Cytokine storm induced new onset depression in patients with COVID-19. A new look into the association between depression and cytokines -two case reports - Orna Alpert; Leonid Begun; Patrik Garren, B.A.; Ramon Solhkhah (Brain, Behavior, & Immunity - Health, 2020)
Background: Depression appears to be a common complication in patients during and post–COVID-19 infection. Understanding the mechanism of action of cytokines such as interleukin-6, interleukin-10 and others in depression and in cytokine storm syndrome, the core component of COVID- 19, could shine a new light on future treatment options for both disorders. Objective: This review demonstrates the role of interleukins in COVID-19 pathogenesis and their role in depression. Results: We described cases we have treated as an example for the dual role interleukins have in COVID-19 infection and depression and reviewed approximately 70 articles focusing on the role of interleukins in cytokine storm syndrome and depression. Conclusion: This review highlights the key features of cytokines in both diseases. As the scientific community has more time to recover and process the effect of the current pandemic, we believe that additional research will pave the way to diverse pathways to treat depression in these patient and others.